Exposure assessment to lead, cadmium, zinc and copper released from ceramic and glass wares intended to come into contact with food - Monika Mania; Tomasz Szynal; Małgorzata Rebeniak; Jacek Postupolski (National Institute of Public Health - National Institute of Hygiene, 2018)
Background. One of the important source of food contamination with elements harmful to human health such as lead or cadmium is migration from the articles intended to come into contact with food. Ceramic and glass articles can also be a source of zinc and copper which compounds are used during the production process of vessels. Objective. Determination of migration of lead, cadmium, zinc and copper from ceramic and glass wares available on the market in Poland and assessment of consumer exposure to these elements. Material and methods. Ceramic and glass articles which were available on the retail market and mainly produced in China were tested for release of lead, cadmium, zinc and copper. Samples for testing were prepared in accordance with European Standards: EN 1388-1 and EN 1388-2 and the migration of elements into a food simulant (4% acetic acid) was measured using flame atomic absorption spectrometry (FAAS). Validated and accredited methods according to EN ISO/IEC 17025:2005 meeting the criteria set in the legislation were applied. Exposure assessment was performed taking into account actual reference doses introduced by the European Food Safety Authority (EFSA) and the Joint FAO/WHO Expert Committee on Food Additives (JECFA). Results. 736 samples of ceramic and glass wares were tested. Among investigated samples for migration of lead 82% of results were below limit of quantification (LOQ = 0.1 mg/L) of the analytical method used. For cadmium zinc and copper results below LOQ were found in 94%, 79% and 100% tested samples, respectively (Cd LOQ = 0.01mg/L; Zn LOQ = 0.05 mg/L; Cu LOQ = 0.03 mg/L). Only one sample release lead in amount higher than limit set in Polish Standard PN-B-13210:1997, it was rim of the glass mug and migration value was 4.81 mg/article. In case of cadmium there were two samples which exceeded permissible migration limit, it was flat ceramic dish and the rim of the glass mug, migration values were: 0.14 mg/dm2 and 0.42 mg/article respectively. The most measurable results (above LOQ) in case of lead and cadmium were for the samples of ceramic and glass drinking vessels. Quantifiable amounts of zinc were found also in other groups of articles tested: flat and deep ceramic dishes. None of the tested articles released copper in amount higher than LOQ value. The risk assessment showed that lead and cadmium exposure for some of the samples far exceed the reference doses. For children, assuming a single use only of these vessels, these doses may be exceeded: in the case of lead, 69 times and in the case of cadmium, 8 times. Conclusions. It is the urgent need to introduce requirements into the applicable legislation for the rim area of drinking ceramic and glass vessels to reduce exposure especially by the most vulnerable groups of population such as children